Ochrona życia prywatnego człowieka - Kubiński, Krzysztof W. (Wydział Prawa i Administracji UAM, 1993)
The article investigates the problems of the protection of t h e right to privacy in the Polish civil law. The right to privacy is not expressis verbis recognized in Polish legislation. Therefore, the introduction of such right into the open catalogue of personality rights defined in the Civil Code brings about a series of questions, the answers to which are the subject-matter of the article. The most important of such questions are the following: 1. what rationale speaks in favour of the introduction of such rights into the catalogue set forth in the Civil Code? 2. whether the right to privacy is to be a superior right, protecting many individual (subordinate) rights, or whether it is to be a separate right? 3. how (through what means) the privacy is to be protected? 4. whether the scope of protection should be identical with respect to all individuals, or whether it should depend on specific features characterizing an individual?.
The protection of right to privacy